Comparative analysis of spore-pollen complexes of coltsfoot crude drug (Tussilaginis farfarae folia) of different ecologicalgeographical origin - Rylova, Tatyana B.; Pazniak, Siarhei S.; Konopelko, Olga M.; Khokh, Anna N. (Journal of the Belarusian State University. Ecology, 2018)
The composition of spore-pollen complexes of samples of the same dried and crushed vegetable raw materials of coltsfoot leaves (Tussilaginis farfarae folia) of different manufacturers was analized. As a result, it was shown that the samples of each producer differ in the composition of the dominant pollen taxa, as well as in the percentage ratio of dominant taxa, i.e. there are clear differences in a number of features specific to a particular manufacturer. At the same time, samples from each individual batch have an almost identical set of characteristics specific only for this batch of plant raw materials.
Keywords: spore-pollen complexes; crude drug; ecological-geographical origin; qualitative and quantitative characteristics; batch; dominant pollen taxons